Cognitive and Affective Control in Insomnia - Schmidt, Ralph E.; Harvey, Allison G.; Van Der Linden, Martial (Frontiers in Psychology, 2011)
Insomnia is a prevalent disabling chronic disorder. The aim of this paper is fourfold: (a) to review evidence suggesting that dysfunctional forms of cognitive control, such as thought suppression, worry, rumination, and imagery control, are associated with sleep disturbance; (b) to review a new budding field of scientific investigation―the role of dysfunctional affect control in sleep disturbance, such as problems with down-regulating negative and positive affective states; (c) to review evidence that sleep disturbance can impair next-day affect control; and (d) to outline, on the basis of the reviewed evidence, how the repetitive-thought literature and the affective science literature can be combined to further understanding of, and intervention for, insomnia.